In Situ Investigation of TCP Phase Formation, Stress Relaxation and gamma/gamma ' Lattice Misfit Evolution in Fourth Generation Single Crystal Ni-Base Superalloys by X-Ray High Temperature Diffraction - Bezold, Andreas; Stone, H. J.; Rae, C. M. F.; Neumeier, Steffen (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2022)
In nickel-based superalloys, the lattice misfit between the gamma and gamma' phases and the propensity to TCP phase formation at service temperatures critically influence the microstructural evolution that takes place and hence the resultant mechanical properties. In this work, the lattice misfits of a series of highly alloyed Ru-containing 4th generation Ni-base superalloys are investigated by in situ X-ray diffraction (XRD) at high temperature. While the lattice misfit values of all alloys range between - 0.3 and - 1.3 pct at room temperature, they show an atypical temperature dependence, becoming less negative above 900 degrees C. In situ XRD measurements at 1100 degrees C reveal that the majority of the internal coherency stresses are already relieved after two hours. This is particularly pronounced for the alloys that have both a lattice misfit larger than vertical bar 0.6 vertical bar pct at 1100 degrees C and are prone to TCP phase formation. However, throughout the relaxation of the internal coherency stresses the lattice misfit remains fairly constant. Due to the similar chemical compositions of the alloys studied, qualitative guidelines for an optimum lattice misfit magnitude are developed by comparing the lattice misfit values with previous creep experiments. Our results indicate that no universal optimal lattice misfit value exists for these alloys and the value strongly depends on the applied creep conditions.
CRIS-Team WoS Importer:2022-05-27